Telaah Komparatif Metode Kritik á¸¤adÄ«th SunnÄ« ala Muá¸¥ammad al-GhazÄlÄ« dan AbÅ« Jaâ€˜far Muá¸¥ammad b. Yaâ€˜qÅ«b al-KulaynÄ« ala ShÄ«â€˜ah - Busairi Busairi (Islamika Inside: Jurnal Keislaman dan Humaniora, 2017)
This article analyzes the method of criticizing the á¸¥adÄ«th offered by Muá¸¥ammad al-GhazÄlÄ« from SunnÄ« school and AbÅ« Jaâ€˜far Muá¸¥ammad b. Yaâ€˜qÅ«b al-KulaynÄ« from Shiâ€˜ite school. The focus of the problem in this study is the difference in the qualifications of hadiths between SunnÄ« and Shiâ€˜ite schools which are the two largest Islamic schools which always have a theological and political contradiction between the two. From these two figures, it can be concluded that there is an equal method of criticism, which is located in the narrator must be á¸Äbit and thiqqah. Besides that there are also differences between al-GhazÄlÄ« that does not require the connection of narrators and emphasizes more on critical criticism. Whereas al-KulaynÄ« requires his sanad to be continued, where he equalizes the infallible priest with the Prophet. The criterion is more to the criticism of sanad. The same criteria in the criticism method can facilitate tracking of authentic á¸¥adÄ«th. Likewise with the different methods of criticism, many traditions are considered valid by the Sunnis but daâ€˜Ä«f according to the Shiâ€˜a and vice versa.